Evaluation of one-stage management of left side cancer colon - Sabry, Mohammed; El-Meligi, Mohammed H.; Elnajar, Mostafa M. (International Surgery Journal, 2018)
Background: Colorectal cancer in Egypt remains a heavy burden as about 40% of cases occur in individuals under 40years of age. The one-stage resection and anastomosis surgery on the left colon due to carcinomas was lately proposed to be safely done. Aim of the work was to evaluate the immediate results of the one-stage resection and anastomosis surgery procedure for left colonic cancer patients and analyzing the relationship between occurrence of complications and clinico-pathological circumstances. Methods: This is a prospective clinical study included 20 patients with mean age 59.4years (70% males and 30% females) having left side cancer colon. All patients underwent history taking, clinical examination and one-stage resection and anastomosis surgery. Results: High percentage of leakage was noticed in females >50years, in diabetics, adenocarcinoma and ischemic heart disease. The leakage rate increased in those who stayed more in the hospital and decreased with the intraoperative preparation. High death rate was noticed in females >50years and in diabetic patients with ischemic heart disease, adenocarcinoma, and obstructed colon. The pre and intraoperative preparation decreased the risk of death. High percentage of wound infection was noticed in males <50years and in diabetic patients with adenocarcinoma and obstructed colon. The risk of wound infection was increased in patients who received intraoperative preparation and who stayed a week or less in the hospital. Conclusions: The incidence of postoperative complications was sound within values generally reported in other studies. Nonetheless, more effort is required to determine risk factors for such postoperative complications to improve the long-term as well as short-term survival in colorectal cancer patients.